Modelling two-phase flow and transport effects of multi-component fuels - Maru, Wessenu-Abegaz (Cranfield University, 2005)
Three novel multicomponent fuel spray droplet evaporation models are developed by employing the theory of continuous thermodynamics(CT) with the aim of applying them in the design and analysis of various energy conversion devices such as, aircraft jet engines, liquid-fuel rocket engines, diesel engines, and industrial furnaces. The CT methodology seeks to represent complex mixtures - for example,aviation kerosene or JP8 that typically comprise blends of a large number of chemical compounds by using probability distribution functions (PDFs). The components of JP8, which is constituted by the homologous series of paraffin, naphthene, and aromatic hydrocarbons; are each represented by the Pearson-Shultz type three-parameter gamma PDF, where the three (shape, scale, and origin) parameters characterise changes in the mixture composition. The phase transition of the liquid droplet due to evaporation is modelled using both low-pressure (LP) and high-pressure (HP) vapour-liquid equilibrium (VLE) models employing various mixing and combining rules by applying a general cubic equation of state (CEOS). Interestingly enough, the phase transition of the liquid fuel into vapour mixture is characterised by a change in the PDF scale parameter alone. Once the description of the fuel mixture is complete, the traditional species and energy transport equations both for the liquid and vapour phases respectively, are re-written using the composition PDF moments under Lagrangian and Eulerian frameworks. In order to solve the governing equations for the three droplet evaporation models, which characteristically involve phase change and a moving interface, a novel fully Adaptive Method Of Lines using B-Spline Collocation (AMOLBSC) is developed. The models are tested at various pressures, temperatures and convective conditions, including at a lean, premixed, prevaporised (LPP) combustor operating condition. In general, the computational results at an ambient pressure close to atmospheric showed good to excellent agreement against available experimental data in the literature. However, for ambient conditions with elevated-high pressures and temperatures only models that employ the HP formulation gave reliable results. In particular, when the liquid is at or near its critical pressure and temperature it is characterised by faster vaporisation and shorter droplet lifetime, including some evidence of liquid mass diffusion. The liquid model that incorporates the effects of liquid core circulation using semiempirical approximation and adaptive mesh refinement (AMR) technique is the most accurate and computationally efficient, although further work is required to establish its ranges of applicability.